BEPS 2.0 Pillar I solutions on mechanisms of tax dispute resolutions - Małgorzata Duda-Plesińska (Prawo Budżetowe Państwa i Samorządu)
The purpose of the article is to present the basic assumptions of Pillar I of BEPS 2.0 and to identify areas of potential disputes on the background of the application of the new mechanisms. The article will briefly outline preventive mechanisms aimed at ensuring tax certainty in connection with the application of the new regulations, as well as mechanisms for eliminating double taxation. The currently available international tax disputes mechanisms will be discussed. The subject of the remainder of the article will be an analysis of the extent to which these mechanisms can serve to resolve disputes arising from the application of Pillar I solutions, and to what extent the implementation of the new rules for the allocation of taxing rights between states with respect to the business income of multinational enterprises will require the introduction of new regulations and what solutions have already been proposed in this matter.